Understanding the Distribution of BPLPL Cards: All-India and Selected States - F Ram, S K Mohanty, Usha Ram (Economic & Political Weekly EPW february 14, 2009 vol xliv no 7, 2009)
Using the recent National Family and Health Survey-3 data, this paper examines the distribution of below poverty line cards. The possession of bpl cards by the households in various economic and social settings index is analysed. The findings suggest that about two-fifths of the bpl cards in India are with the non-poor households. On the other hand, in many of the states a majority of households in abject deprived groups do not possess a bpl card. The extent of misuse is higher in Andhra Pradesh, Karnataka and Kerala, while it is lower in Tamil Nadu. In economically weaker states like Orissa and Bihar, a higher proportion of non-poor households possess a bpl card